Accounting Reports With Time as a Variable. - Nichols, Arthur C.; Grawoig, Dennis E. (The Accounting Review, 1968)
Abstract Providing purpose oriented information appears to become an important part of the accountant's function in the future. With the increasing utilization of the computer in carrying out many of his past functions, this role may even be crucial to the accountant's professional survival. However, before the accountant can fulfill this role, methods of drawing information of different types from the available financial data must be developed. This article has provided some basic research for attacking this problem through the removal of the traditional assumption of a fixed time dimension in accounting reports. It was found that when this assumption was relaxed, quite different information was provided by identical financial data. It is not the intention of this article to suggest that the traditional method of reporting financial data be superseded by an alternative method. The purpose of this article is rather an attempt to uncover new avenues for possible improvements in financial reporting by emphasizing the varied types of information available from financial data and by showing the ever present characteristic of quantitative information to portray certain relation- ships while concealing others.